Faktor-Faktor Keputusan Nasabah menggunakan Produk Perbankan Bank Syariah Indonesia di Kota Jambi - Afriantoni Afriantoni (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS GRAHA KARYA MUARA BULIAN, 2021)
This study aims to determine the factors of customer decisions in using Indonesian Islamic banking products. This type of research is research with quantitative data types. Sources of data in this study came from primary data and secondary data. The sample of this study was 100 respondents who were taken by survey, namely research that used a questionnaire as a research instrument. The method of analysis and the data uses a validity test, with a Liker scale approach. Based on the results of the tests carried out. From the results of the data validity test that r count > r table of each service variable (X1), bank characteristics (X2), knowledge (X3), location (X4), it is explained that from each statement each variable is stated valid. The most influential factors are Bank Characteristics with an index of 4.77 (very good).